Clinicopathologic features of metastatic small cell carcinoma of the prostate to the liver: a series of four cases - Phoenix D. Bell; Aaron R. Huber; Diana Agostini-Vulaj (BMC, 2021)
Abstract Background Small cell neuroendocrine carcinoma of the prostate (SCNECP) is a rare, aggressive subtype of prostate carcinoma. Most SCNECP arise from conventional prostate adenocarcinoma (CPAC) treated with androgen deprivation therapy (ADT). Case presentations We identified four cases of CPAC treated with ADT, which evolved to SCNECP with liver metastasis. The average interval between the diagnosis of CPAC and SCNECP was 102 months (range: 12 to 168). Histologically, the tumors showed nests of cells with high nuclear:cytoplasmic ratios, granular chromatin, and frequent mitoses. All cases were synaptophysin, chromogranin, and AE1/AE3 positive, with a Ki-67 labeling index ≥70%. NKX3.1 was negative in all but one case and TTF-1 was positive in half. Weak ERG positivity by IHC was seen in one case which also demonstrated the TMPRSS2-ERG gene rearrangement; all other cases were negative for ERG by IHC. Serum prostate specific antigen (PSA) levels were normal to near-normal in all. The median interval between the diagnosis of SCNECP and death was 3.25 months (range: 0.75 to 26). Conclusions Our case series highlights the importance of considering a prostate primary, even in the setting of normal PSA levels and loss of prostate markers, when diagnosing neuroendocrine carcinoma in the liver. Further, we emphasize the significance of diagnosing SCNECP that metastasizes to the liver, as it portends a particularly dismal prognosis.